Digital Assets in the Perspective of Indonesian Inheritance Law: The Need for Norm Reformulation in the Cyber Era - Anisa Ayu Dwi Lestari (Politeknik Siber Cerdika Internasional, 2025)
The development of digital technology has created new forms of wealth in the form of digital assets such as crypto wallets, social media accounts, and cloud data storage. However, the inheritance law system in Indonesia, both regulated in the Civil Code and the Compilation of Islamic Law (KHI), has not accommodated the inheritance of digital assets explicitly. This creates a legal vacuum that results in the loss of heir rights and difficulty in accessing these assets after the death of the owner. This research aims to: (1) identify the types of digital assets that are relevant in the context of inheritance; (2) analyze the suitability of Indonesian inheritance law for the challenges of digital inheritance; and (3) formulate the direction of reformulation of inheritance law norms to be adaptive to technological developments. The research used a juridical-normative method with a comparative approach. Data was collected through literature study, legal document analysis, and interviews with notaries, academics, and judicial practitioners. The results show that digital assets have significant legal and economic value, but have not received explicit recognition as an object of inheritance in the national legal system. The practice of inheriting digital assets is still informal and does not have permanent legal force. Therefore, reformulation of Indonesian inheritance law norms is needed through recognition of digital assets as objects of inheritance, regulation of digital wills (e-wills), and integration with the principles of personal data protection.